OP0125 Gender-specific differences in adamantiades-behÇet's disease presentation: Meta-analyses of combined data from the german registry for adamantiades-behÇet's disease and from a systematic literature review. (23rd January 2014) - Luong Nguyen, L.B.; Bonitsis, N.G.; Altenburg, A.; Zouboulis, C.C.; Mahr, A.
Abstract : Background: Adamantiades-Behçet's disease (ABD) is a multisystem disorder characterized by highly variable presentations. The factors driving the individual disease expressions are not well known. Differences in clinical features between males and females, which would point to gender-specific pathogenic mechanisms, have been described but they remain ill-defined. Objectives: To investigate the effect of gender on clinical ABD phenotype using meta-analyses of the data from a national patient registry for ABD combined with observation data identified by a comprehensive literature review. Methods: Relevant publications were identified by a systematic literature research using PubMed MEDLINE and Embase. Eligible studies had to provide comparative frequencies for at least 3 BD characteristics stratified by gender. Furthermore, the extracted data were grouped with those from the German Registry for ABD, a national, multicenter registry prospectively collecting demographic and clinical information for ABD patients since 1990. Pooled relative risks (RR) were calculated for those variables for which at least 10 relevant studies were identified. Computations used random-effects models and between-study variability was assessed with I 2 statistics. Results: Among the 633 publications evaluated, 27 studies met eligibility criteria. The German Registry for ABD provided information for an additional 721 subjects. Pooled RR [95% confidence intervals], representing the risk for male compared with female ABD to present with any of the 15 analyzed disease characteristics, were as follows: genital ulcers (27 comparisons): RR: 0.95 [0.91–0.99] ( P sig = 0.02, I 2 =69.5%); eye involvement (27 comparisons): RR: 1.34 [1.22–1.46] ( P sig < 0.0001, I 2 =66.7%); skin involvement (16 comparisons): 1.01 [0.93–1.10] ( P sig = 0.80, I 2 =66.7%); papulopustular lesions (10 comparisons): 1.23 [1.15–1.33] ( P sig < 0.0001, I 2 =25.6%); pseudofolliculitis (11 comparisons): 1.38 [1.13–1.68] ( P sig = 0.002, I 2 =72.9%); erythema nodosum (18 comparisons): RR: 0.82 [0.75–0.89] ( P sig < 0.0001, I 2 =58.9%); positive pathergy test (13 comparisons): 1.07 [0.98–1.16] ( P sig = 0.14, I 2 =45.4%); joint involvement (27 comparisons): RR: 0.83 [0.75–0.90] ( P sig < 0.0001, I 2 =61.2%); vascular involvement (16 comparisons): 2.52 [1.74–3.65] ( P sig < 0.0001, I 2 =71.5%); superficial thrombophlebitis (9 comparisons): 1.91 [1.04–3.50] ( P sig = 0.04, I 2 =88.6%); deep vein thrombophlebitis (13 comparisons): 2.55 [1.68–3.86] ( P sig < 0.0001, I 2 =63.1%); arterial involvement (9 comparisons): RR: 1.30 [0.67–2.51] ( P sig = 0.44, I 2 =26.7%); CNS involvement (27 comparisons): RR: 1.05 [0.85–1.30] ( P sig = 0.63, I 2 =48.2%); gastrointestinal involvement (20 comparisons): RR: 0.84 [0.64–1.10] ( P sig = 0.21, I 2 =48.4%) and lung involvement (10 comparisons): RR: 1.32 [0.71–2.47] ( P sig = 0.38, I 2 =33.3%). Conclusions: ABD in males is associated with a slightly higher prevalence of eye involvement, pseudopustular lesions and pseudofolliculitis, and a 2–2.5-fold higher prevalence of vascular involvement, and particularly of thrombophlebitis. In contrast, female ABD is characterized by slightly more common genital ulcers, erythema nodosum and joint involvement. These findings may provide further clues to the mechanisms underlying the physiopathology of ABD. Disclosure of Interest: None Declared